A multi-criteria performance analysis of Initial Public Offering (IPO) firms using CRITIC and VIKOR methods - Yalçin, Neşe; Ünlü, Ulaş (Technological and Economic Development of Economy, 2018)
As Initial Public Offering (IPO) is a significant milestone in the financial strategy of a firm, this study aims to evaluate performance of IPOs using multiple measures including accounting-based performance (ABP), value-based performance (VBP) and overall performance (OP) in the pre-and post-IPO periods. Therefore, we present two combined approaches based on a compromise MCDM method-VIKOR and objective weighting methods-CRITIC and MW (Mean Weight) to evaluate and rank IPOs to help shareholders with understanding on how their performance changes under the different measures. Since the compromise solution (one or a set) proposed by VIKOR depends substantially on criteria weights, VIKOR-CRITIC can show more realistic results because of the differential weights assigned to criteria by CRITIC. In this study, a case study is conducted in order to evaluate the performance of Turkish IPOs based on ABP, VBP and OP measures using the combined methods. The results show that the compromise solution results obtained by VIKOR-CRITIC may be a guideline for investors in making more profitable investment decisions before leaping into any investment decision. First published online: 27 Mar 2017